Performance of a score to characterise adequate contact among the social network of persons with TB - M.E. Castellanos; S. Zalwango; T.H.T. Quach; R. Kakaire; L. Martínez; M.H. Ebell; K.K. Dobbin; N. Kiwanuka; C.C. Whalen (IJTLD Open)
BACKGROUND: Transmission of Mycobacterium tuberculosis requires adequate contact between an infectious case and a susceptible host. The aim of this analysis was to validate a recently developed contact score that assessed settings of exposure and relationships between the case and contact. METHODS: In a cross-sectional study from Kampala, Uganda, we estimated the prevalence of tuberculous infection (TBI) in social contacts of adult TB cases according to the setting and relationship domains of the contact score. We calculated the prevalence ratio (PR) for the association between contact scores (by domain) with TBI using modified Poisson regression models. RESULTS: We enrolled 955 household and community contacts from 119 TB cases. The prevalence of TBI in the social network was 52% (95% CI 48–55). The prevalence of TBI increased by quartile for both the setting score (44%, 40%, 53%, 70%; P trend <0.0001) and the relationship score (41%, 47%, 53%, 66%; P trend <0.0001). The setting score was associated with a higher prevalence of infection among children aged 5–14 years, whereas the relationship score was associated with infection in children aged 0–4 years. CONCLUSION: In urban Africa, contacts of TB with higher settings and relationship scores were more likely infected with M. tuberculosis.